جهود علماء سجستان في الحديث وعلومه: دراسة تحليلية - حريد، كلثوم محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This thesis focuses on the great contributions of Muslim scholars in Sijistan toward ‎the hadith and related sciences. For that matter , the areas of information and ‎discussion covered in the thesis include: the physical, geographical, and climatic ‎introduction to the Sijistan region, the history of Sijistan right from its conquest by ‎Muslims until its destruction in the seventh century after hijrah, the academic ‎movement in Sijistan, the centres of learning in general and religious as well as ‎empirical expertise of the people in Sijistan in particular, the entry of the ‎Companions and the Successors into the region, who became the originators of hadith ‎Studies there, the profiles of hadith scholars in Sijistan between the second century ‎and the seventh century after hijrah, the academic activities of Sijstani hadith ‎scholars within the region or outside, the contributions of Sijistani hadith scholars ‎toward the development of two dimensions of hadith Studies, narration and critical ‎investigation, and description of diversified works of Sijistani hadith scholars in the ‎field of hadith and related sciences. The methodology applied in the thesis is four-‎pronged: inductive, descriptive, analytical and historical. The thesis concludes that ‎Sijistan appears as the most significant region due to its great contributions toward ‎the preservation of hadith and development of hadith Studies.‎